DEVELOPMENT AND PRESENTATION OF FINANCIAL STATEMENT IN SMALL AND MEDIUM ENTERPRISES (SMES) BASED ON FINANCIAL ACCOUNTING STANDARDS FOR ENTITIES WITHOUT PUBLIC ACCOUNTABILITY : A QUALITATIVE STUDY - Fima Rahmanela Amanda Putri,; Mohamad Suyunus, (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
One challenges inmicro, small and medium enterprises is preparation and presentation of financial statements in accordance to international standards adopted in Indonesia. However, recording system is not applied with certain factors.